T2Candida assay: diagnostic performance and impact on antifungal prescribing. Issue 2 (6th April 2023) - Patrocínio de Jesus, Rita; Houston, Hamish; Schutte, Annemiek H J; Morris-Jones, Stephen; Stone, Neil; Gorton, Rebecca; Pollara, Gabriele
Abstract: Objectives: To assess the performance of T2Candida for the diagnosis of invasive candidiasis (IC) against gold standards of candidaemia or consensus IC definitions, and to evaluate the impact of T2Candida on antifungal drug prescribing. Methods: A retrospective review was undertaken of all T2Candida (T2MR technology, T2 Biosystems) performed from October 2020 to February 2022. T2Candida performance was evaluated against confirmed candidaemia or against proven/probable IC within 48 hours of T2Candida, and its impact on antifungal drug prescriptions. Results: T2Candida was performed in 61 patients, with 6 (9.8%) positive results. Diagnostic performance of T2Candida against candidaemia had a specificity of 85.7% and negative predictive value (NPV) of 96.8%. When comparing T2Candida results with consensus definitions of IC, the specificity and NPV of T2Candida was respectively 90% (54/60) and 98.2% (54/55) for proven IC, and 91.4% (53/58) and 96.4% (53/55) for proven/probable IC. Antifungals were initiated in three of six patients (50%) with a positive T2Candida result. Thirty-three patients were receiving empirical antifungals at the time of T2Candida testing, and a negative result prompted cessation of antifungals in 11 (33%) patients, compared with 6 (25%) antifungal prescriptions stopped following negative beta-d -glucan (BDG) testing in a control population ( n  = 24). Conclusions: T2Candida shows high specificity and NPV compared with evidence of Candida bloodstream infection or consensus definitions for invasive Candida infection, and may play an adjunctive role as a stewardship tool to limit unnecessary antifungal prescriptions.